The Utilization of Oocyte Cryopreservation Among Indonesia Women - Batara Sirait; Nining Handayani; Ayu Mulia Sundari; Tri Aprilliana Wulandari; Ivan Sini; Arie Adrianus Polim; Muhammad Rizal; Arief Boediono (Jurnal Profesi Medika : Jurnal Kedokteran dan Kesehatan, 2022)
Our study aims to assess the utilization of oocyte cryopreservation (OC) in Indonesian women. Data from 122 women who had undergone OC was retrospectively analyzed from medical records. The baseline profile, clinical characteristics, and main outcomes comprising intentions for oocyte vitrification and outcomes following oocyte warming were examined. Out of 122 women who underwent OC, 49 patients returned and use their cryopreserved oocytes with a median duration of storage was two months. Arranged from the greatest to the least, participants had undergone the cycle of OC due to sperm factor [51 (41.80%)], increased embryo availability [6 (12.1%)], postponement of marriage [6 (12.1%)], social reasons [10 (8.19%)], and other reasons [8 (6.55%)]. Meanwhile, treatment due to advanced maternal age [6 (4.91%)], poor ovarian reserve [6 (4.91%)], cancer [5 (4.09%)], PCOS [2 (1.63%)], and endometriosis [2 (1.63%)] was reported among remaining subjects. Clinical pregnancy was reported in 12 (40.0%) patients constituting of each 6 (50.0%) subjects of day-3 and day-5 embryo transfer, respectively. Our study demonstrated that sperm factor, increased embryo availability, and postponement of marriage is the main reason for women undergoing OC in Indonesia.